PENGARUH KETIDAK PASTIAN LINGKUNGAN DAN ORIENTASI PASAR TERHADAP KINERJA BISNIS DENGAN INOVASI SEBAGAI VARIBEL MEDIATOR (Studi Pada Bank Perkreditan Rakyat Di Solo Raya) - Septiana Novita Dewi; Aris Tri Haryanto (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2016)
The purpose of this study is to create a competitive advantage by maximizing the performance of business organizations is to seek a market-oriented company profile and its impact on innovation in the organization. The target population is 90 rural banks in Solo Raya, while samples taken as many as 45 RBs (50%). Based on the Solo Raya region comprising seven areas, namely Wonogiri, Klaten District, Sragen, Boyolali district, Karanganyar, Sukoharjo regency and municipality Surakarta then each region is taken at random. The results showed environmental uncertainties and no significant negative effect on innovation. Market orientation and significant positive effect on innovation. Environmental uncertainties and significant positive effect on business performance. Market orientation positive and significant impact on business performance. Innovation positive and significant impact on business performance. Environmental uncertainties and market orientation through effective direct path.